逾越节之花 - Rolston, Holmes, 1932-2025, author; Taiwan Ecological Stewardship Association, publisher (Colorado State University. Libraries, 2007)
The Pasqueflower surviving through winter, blooming at the Pasque, Easter, offers a glimpse of the precocious exuberance of life, a token of the covenant of life to continue in beauty despite the wintry storms. To pause at first encountering it in spring is to find a moment of truth, a moment of memory and promise. Let winters come, life will flower on as long as Earth shall last.
Pasqueflower
Yu Yue Jie zhi hua
Text in Chinese.
Keywords: Pasque; exuberance; fruition; spring of life; flowers; flower children; Passover; Easter